Total hip arthroplasty through an anterior approach: The pros and cons. Issue 11 (November 2018) - Kyriakopoulos, Georgios; Poultsides, Lazaros; Christofilopoulos, Panayiotis
Abstract : Total hip arthroplasty through an anterior approach has been increasing in popularity amongst surgeons and patients. Anterior approach hip arthroplasty seems to offer improved early outcomes in terms of pain, rehabilitation and length of stay. No difference in long-term outcomes has been shown between anterior and posterior or lateral approaches. Proper formal training, utilization of fluoroscopy and adequate experience can mitigate risks of complications and improve early and medium-term outcomes. Cite this article: EFORT Open Rev 2018;3:574-583. DOI: 10.1302/2058-5241.3.180023.